THEORY AND MODELS UNDERLYING ETHICAL INVESTMENT RESEARCH - Abdulloh Mubarok,; Mushawir,; Baihaqi Fanani,; Ibnu Muttaqin,; Raihan, Raihan (International Journal of Social Science, 2022)
The purpose of this article is to explore in depth the literature on the theories and models that underlie ethical investment research. Through a literature review study, the research found 10 journals that are ready to be reviewed. The literature search found several theories and models that underlie ethical investment research. The theories and models include agency theory, Angel and Rivoli model (1997), Heinkel, Krause and Zechner model (2001), Barnea, Heinkel and Krause model (2005) and Hypothesis Model of Ethical Investment and Stock Price Relationship of Derwall, Koedijk and Ter Horst (2011).